Effects of ramelteon on cardiac injury and adipose tissue pathology in rats with metabolic syndrome. Issue 1 (15th March 2018) - Uchinaka, Ayako; Kawashima, Yuri; Sano, Yuki; Ito, Shogo; Sano, Yusuke; Nagasawa, Kai; Matsuura, Natsumi; Yoneda, Mamoru; Yamada, Yuichiro; Murohara, Toyoaki; Nagata, Kohzo
Abstract: Melatonin regulates circadian rhythms but also has antioxidative and anti‐inflammatory effects that ameliorate metabolic disorders. We investigated the effects of the selective melatonin agonist ramelteon on cardiac and adipose tissue pathology in the DahlS.Z‐ Lepr fa /Lepr fa (DS/obese) rat, a model of metabolic syndrome (MetS). Rats were treated with a low (0.3 mg/kg per day) or high (8 mg/kg per day) dose of ramelteon from 9 to 13 weeks of age. Ramelteon treatment at either dose attenuated body weight gain, left ventricular fibrosis, and diastolic dysfunction, as well as cardiac oxidative stress and inflammation, without affecting hypertension or insulin resistance. Although ramelteon did not affect visceral white adipose tissue (WAT) mass, it attenuated inflammation and downregulated insulin signaling in this tissue. In contrast, ramelteon reduced fat mass, adipocyte hypertrophy, and inflammation, and ameliorated impaired insulin signaling in subcutaneous WAT. In addition, ramelteon attenuated adipocyte hypertrophy, downregulated mitochondrial uncoupling protein 1, and upregulated 11β‐hydroxysteroid dehydrogenase type 1 expression in interscapular brown adipose tissue (BAT). In summary, ramelteon treatment attenuated obesity and cardiac injury, improved insulin signaling in visceral and subcutaneous WAT, and inhibited the whitening of BAT in rats with MetS.